Nutmeg-Vertebrate Interactions in the Asia-Pacific Region: Importance of Frugivores for Seed Dispersal in Myristicaceae. (November 2013) - Kitamura, Shumpei; Poonswad, Pilai
In tropical forests, large frugivores are assumed to be important seed dispersers for many large-seeded trees such as the Myristicaceae, a widespread and common family. However, not all frugivores are effective seed dispersers, and understanding which frugivores are effective is vital for conservation biology. Here, we summarize the available data on fruit characteristics and frugivores for a large number of Myristicaceae species in the Asia-Pacific region and suggest future directions for evaluating the effects of disperser loss for these trees. Studies of fruit characteristics of Myristicaceae were highly biased toward morphological information, and few studies examined reproductive phenology or fruit chemistry. We identified 338 instances of nutmeg-frugivore interactions that included 129 species of Myristicaceae and 109 species of frugivores, including 40 bird, 68 mammal, and one reptile species. Large birds were major seed dispersers for this tree family. These bird species, such as hornbills and pigeons, consumed a variety of nutmeg species, remained briefly at fruiting trees, and dispersed intact seeds far from the parent trees in the forest. Although most seeds dispersed by birds subsequently suffered high seed predation by rodents, some germinated and established as seedlings, indicating the qualitative effectiveness of large birds as seed dispersers for Myristicaceae. Mammals were also major consumers of Myristicaceae. Gibbons, macaques, and civets potentially acted as long-distance dispersers for some nutmeg species. Orangutans, leaf monkeys, squirrels, and rodents consumed a variety of nutmeg species, but their roles as seed dispersers for Myristicaceae remain unclear. Studies of nutmeg-vertebrate interactions have typically focused on frugivory, whereas few studies have specifically quantified the effectiveness of frugivores as seed dispersers; thus, it remains difficult to evaluate the effect of frugivore loss on the populations of most nutmeg species in this region. Further studies of nutmeg-frugivore interactions are of great ecological importance, and the results of such studies will contribute to a general understanding of which evolutionary forces may have shaped current nutmeg-frugivore interactions in tropical forests worldwide.